Determination of thermal conductivity, thermal diffusivity and specific heat capacity of porous silicon thin films using the 3ω method. (March 2022) - Erfantalab, Sobhan; Parish, Giacinta; Keating, Adrian
Highlights: Demonstration that a low noise, extended frequency range (100 Hz- 33 kHz) 3ω measurement coupled with a multilayer thermal model allows simultaneous measurement of both thermal conductivity and thermal diffusivity. Demonstration that using this method, thermal conductivity and thermal diffusivity can be determined for low thermal conductivity films attached to high conductivity substrates, validated using bulk glass and thin SU-8 films (1.35 to 12.5 µm). The ability to simultaneously measure thermal conductivity and thermal diffusivity in porous silicon thin films while still attached to a silicon substrate enables the determination of heat capacity of these thin films, an improvement on the assumptions required for other methods. The finding that a monotonic increase in specific heat capacity of porous silicon films exists which is a function of porosity, an effect previously reported only for nanoporous Al2 O3 films. Abstract: Here the thermal transport properties of low thermal conductivity porous silicon thin films attached to high thermal conductivity silicon substrates are studied using the 3 ω method implemented over the 100 Hz to 33 kHz frequency range. The thermal conductivity and thermal diffusivity of the films are extracted using temperature impedance monitoring of electrical contacts deposited on films, combined with an extended-frequency, multi-layer thermal model. From the extracted thermal conductivity and diffusivity of the films, the heat capacity could be determined. Validation of the approach is performed using the known properties of thick substrate glass and SU-8 layers spun on silicon substrates, the latter ranging in thickness from 1.35 to 12.5 µm. The technique was then applied to porous silicon films with porosities ranging from 45% to 77%. The extracted thermal properties for as-fabricated films show a reduction of thermal conductivity and diffusivity from 1.7 to 0.15 W/mK and 1.9 to 0.2 mm 2 /s, respectively as the porosity increases. After passivation by annealing in nitrogen and at 600 °C, the same films exhibited higher values of thermal conductivity and diffusivity ranging from 2.7 to 0.7 W/mK and 2.5 to 0.65 mm 2 /s. The ability to extract both thermal conductivity and thermal diffusivity for these films removes the need to make assumptions around specific heat capacity, commonly made during analysis of porous media. These results show for the first time a monotonic increase in specific heat capacity of porous silicon films as a function of porosity.